THE EFFECTIVENESS AND ROLE OF EDUCATORS IN THE IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM - Aditya Kusuma Sumantri (Journal of Curriculum and Pedagogic Studies (JCPS), 2023)
Effectiveness in learning is certainly an important thing, but when viewed from the developments that exist in the world of education and also the role of educators that are increasingly changing today, it is very important to discuss the effectiveness and role of educators in the independent learning curriculum. Educators as drivers of independent learning, mean an educator who is required to be able to be active and enthusiastic, creative, innovative and skilled to become a facilitator of change drivers in schools. The purpose of writing this article is to discuss the effectiveness of learning and the role of the educators themselves, especially in the use of the independent learning curriculum as it is today. Then related to the data source used is a form of litelatur related to the theme, be it in the form of books, articles, journals, and other writing sources on the internet. The method used is a library research method by finding and collecting relevant sources, then filtering the sources that are most relevant to the theme to be studied or raised, then making conclusions and recording various important things, and then later implemented in writing form. Keywords: Effectiveness, The Role of Educators, Independent Learning Curriculum